2018
DOI: 10.1021/acssuschemeng.8b01758
|View full text |Cite
|
Sign up to set email alerts
|

Switchable Aqueous Pentaethylenehexamine System for CO2 Capture: An Alternative Technology with Industrial Potential

Abstract: Herein we report the application of polyamine pentaethylenehexamine (PEHA, 3,6,9,12-tetraazatetradecane-1,14-diamine) in CO2 absorption with both neat PEHA and aqueous solutions thereof. The absorption of molecular CO2 in pure PEHA and in PEHA-water systems resulted in the formation of two chemical species, namely, PEHA carbamate and bicarbonate. It was observed that, upon formation of these species, both the CO2 absorption capacity and CO2 absorption rate were controlled by the amount of water in the system. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…Increasing the temperature naturally weakens the intermolecular bonds, leading to increased fluidity and decreased density. The higher viscosity and density of the 25% PEHAp solution could be related to intermolecular hydrogen bonding with higher strength between water and PEHA compared to intra- and intermolecular hydrogen bonding in PEHA . The 25% PEHA solution displayed a viscosity of 5.6 mPa·s at 20 °C (data not shown), which can be compared to 4.2 mPa·s for 25% PEHAp.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…Increasing the temperature naturally weakens the intermolecular bonds, leading to increased fluidity and decreased density. The higher viscosity and density of the 25% PEHAp solution could be related to intermolecular hydrogen bonding with higher strength between water and PEHA compared to intra- and intermolecular hydrogen bonding in PEHA . The 25% PEHA solution displayed a viscosity of 5.6 mPa·s at 20 °C (data not shown), which can be compared to 4.2 mPa·s for 25% PEHAp.…”
Section: Resultssupporting
confidence: 89%
“…The higher viscosity and density of the 25% PEHAp solution could be related to intermolecular hydrogen bonding with higher strength between water and PEHA compared to intra-and intermolecular hydrogen bonding in PEHA. 22 The 25% PEHA solution displayed a viscosity of It can generally be observed that the initial absorption rates for 25% PEHA and 25% MEA are the highest, where PEHA displayed the highest overall absorption rate. In contrast to the other solutions, the 25% PEHA and MEA solutions also maintained a high absorption rate over a larger CO2 load (mol L -1 ) interval, which is consistent with the availability of a high number of strong primary and secondary amines per unit volume ( Figure 4A).…”
Section: Structural Characterization Was Done By Nmr Spectroscopy Permentioning
confidence: 91%
See 3 more Smart Citations